Influence of drug adherence and medical care on heart failure outcome in the primary care setting in Austria†. (18th May 2015) - Marzluf, Beatrice A.; Reichardt, Berthold; Neuhofer, Lisa M.; Kogler, Bernhard; Wolzt, Michael
Abstract Purpose Guideline‐recommended therapy has been proven beneficial in heart failure (HF), but general implementation remains poor. The aim of this study was to evaluate the adherence to drug therapy, quality of primary non‐drug medical care (NDMC) and its impact on HF outcome. Methods From 13 Austrian health insurance funds, we identified 36 829 patients (77.1 ± 10.8 years, 44.8% men) hospitalised for HF who survived more than 90 days after discharge in the period between April 2006 and June 2010. Drug adherence was analysed from prescriptions filled and NDMC from numbers of physician consultations and diagnostic tests relevant for HF per quarter of a year (medical care index (MedCI)) claimed from the insurance funds. Kaplan–Meier and multivariate Cox regression analyses were performed to identify the association of outcome (survival and death without further admission for HF, readmission for HF) with drug adherence and NDMC. Results Readmission due to HF or death without prior readmission for HF occurred in 19.7% and 22.5%, respectively. Adherence to angiotensin‐converting‐enzyme inhibitors or angiotensin receptor blockers, beta‐blockers and aldosterone antagonists was 49.3%, 40.4% and 16.1%, respectively, and was associated with better survival by Kaplan–Meier analysis. NDMC was consumed less frequently by deceased (76.0%; MedCI 2.55 ± 3.04) than surviving (79.3%; 3.60 ± 3.81) or readmitted (78.4%; 3.80 ± 4.13) patients (p < 0.001 for deceased vs both other). Drug adherence and NDMC were independent factors associated with better survival by multivariate regression analysis. Conclusion Guideline‐recommended drug therapy remains underutilised in Austria. Drug adherence and quality of NDMC are associated with better outcome in HF patients. Copyright © 2015 John Wiley & Sons, Ltd.